Endovascular Aneurysm Sealing: Early and Midterm Results From the EVAS FORWARD Global Registry. (October 2016) - Thompson, Matt M.; Heyligers, Jan M.; Hayes, Paul D.; Reijnen, Michel M. P. J.; Böckler, Dittmar; Schelzig, Hubert; de Vries, Jean-Paul P. M.; Krievins, Dainis; Holden, Andrew; ,
Purpose: To report the early and 12-month results of a global registry of patients treated with endovascular aneurysm sealing (EVAS) for abdominal aortic aneurysms (AAAs).Methods: The EVAS FORWARD Global Registry was a postmarket, multicenter, open-label, single-arm registry that enrolled 277 patients (mean age 75 years; 228 men) treated with the Nellix EVAS system for nonruptured AAAs at 18 sites over a 1-year period. The cohort had challenging aortic anatomy, with 17% having a proximal aortic neck length <10 mm, 8% a neck angulation >60°, and 20% an iliac diameter >25 mm. Baseline and follow-up computed tomography images were assessed by an independent core laboratory, and major adverse events were reviewed by an independent safety committee.Results: Three patients died within 30 days of the procedure (none device-related). There were 13 endoleaks recorded in this time frame: 8 type Ia, 1 type Ib, and 5 type II. Root cause analysis demonstrated that the majority of type Ia endoleaks were due to technical error (low device placement and underfilling of the endobags). Between 30 days and 1 year, there were 4 new type Ia endoleaks; all were treated. There was also 1 type III endoleak between a Nellix device and a distal extension limb. At 1 year, the persistent endoleak rate was 0.7% (1 type Ia and 1 type II). The Kaplan-Meier estimates of freedom from types I and II endoleak at 12-month follow-up were 96% and 98%, respectively. The estimate of freedom from open conversion (n=7) was 98% at 12 months and the rate of freedom from any reintervention was 92%. The need for secondary intervention was associated with aortic morphology; for patients meeting the requirements of the instructions for use (IFU), the freedom from reintervention at 12 months was 98% compared with 86% when the implant was outside the IFU (p=0.009). At 1 year, the estimates of freedom from aortic-related and all-cause mortality were 98% and 95%, respectively.Conclusion: The EVAS FORWARD Global Registry documents the 12-month outcome of EVAS in an unselected group of patients with challenging aortic morphology. The results at present appear acceptable with regard to perioperative outcomes and complications. The type II endoleak rate is low. The place of EVAS in the armamentarium of techniques to treat AAAs will be defined by durability data in the longer term.